Esterase activities and biochemical properties of lactic acid bacteria isolated from goat´s milk cheese in Argentina - Taboada, Natalia Verónica (2014)
Twenty-two lactic acid bacteria (LAB) strains isolated from Argentinean goat dairy products were evaluated for its biochemical properties and esterase activities relevant to flavor development. Streptococcus thermophiles (UNSE314), Lactobacillus (L.) delbrueckii subsp. bulgaricus (UNSE309), L. rhamnosus (UNSE308), L. plantarum (UNSE287, UNSE316, UNSE317) and Pediococcus pentosaceus (UNSE315) strains presented high acidifying activity. All strains tested metabolized citrate and produced diacetyl-acetoin in goat milk. Based on these results, ten strains with the best performance in diverse technological properties were selected to determine esterolytic activity. In all evaluated strains, esterase specific activity (ESA) was detected on a-naphthyl (a-NA) acetate and B-naphthyl (B-NA) acetate, propionate, caprylate and a-NA butyrate. No activity was detected on B-NA laurate. The highest values were detected when using a-NA instead of B-NA derivatives as substrate. In Pediococcus strains, wide variability in ESA were observed, which were species- and strain-specific. These results allow us to select strains with biochemical properties and esterase activities to design starter and adjunct cultures that contribute to flavor development during cheese ripening, thus preserving the typical organoleptic characteristics of Argentinean goat cheeses.